Sejarah dan Perkembangan Psikologi Islam: Dari Perspektif Al-Qur’an, Pemikiran Ulama Klasik hingga Kajian Psikologi Modern - Selvi Khansa Lutfiyah; Clarisa Dwinanda Febriani; Akmal Rizki Gunawan Hasibuan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Islamic Psychology is a discipline that emerged in response to the limitations of modern psychology in explaining human beings comprehensively, particularly regarding spiritual and religious dimensions. This article aims to examine the history and development of Islamic Psychology, from the ideas of classical Muslim scholars to the advancement of modern Islamic Psychology studies, as well as its contributions to contemporary psychology. This study employed a Systematic Literature Review method by analyzing various relevant scientific sources. The findings indicate that Islamic Psychology has developed since the classical Islamic civilization through the contributions of scholars such as Al-Kindi, Al-Farabi, Ibn Sina, Al-Ghazali, and Ibn Arabi. In the modern era, the development of Islamic Psychology has been marked by the Islamization of knowledge movement, the integration of modern psychology with Islamic values, and the contributions of contemporary Muslim thinkers. Furthermore, Islamic Psychology contributes to contemporary psychology through the development of psychotherapeutic approaches and psychological interventions that integrate scientific and spiritual aspects. Therefore, Islamic Psychology offers a holistic perspective in understanding human beings and remains highly relevant in addressing various mental health challenges in the modern era.